Analisis Kekeliruan Pengungkapan Objek Matematika dalam Buku Teks Kelas I SMU - Abdul Hamid (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
Mathematic object consists of facts, concepts, principles and operations, which are the major of instructional material to improve students' transferable competence. The discussed problem is whether mathematic objects in textbook have been presented correctly. To answer this question, the writer uses content analysis. The analysis technique applied is the analysis among books using interactive model. The result of this research shows that the five analyzed books (TS, EL, PB, PR, and YT) have errors in presenting mathematic objects.